Experimental study and application of hydraulic fracturing in underlying coal seam - Yongxin LU; Shengyong HU; Guofu LI; Xi WU; Jiaqi LU; Yutao YANG; Cun ZHANG; Yan SU (Meitan kexue jishu, 2024)
The coalbed methane resource under goaf is rich, but has not been effectively developed for a long time. Hydraulic fracturing technology stands as an effective means to augment coalbed methane recovery. The extraction and re-compaction of overlying coal seam will directly affect the expansion behavior of hydraulic fractures in the underlying coal seam. Though the large-scale (300 mm×300 mm×300 mm) true triaxial hydraulic fracturing experiments, the mechanical and acoustic emission response characteristics of coal were analyzed under different levels of loading and unloading stress perturbations. The damage variable T was proposed to characterize the degree of coal damage, and the relationship between damage and the initiation and expansion patterns of hydraulic fractures was elucidated. The results revealed that, the damage induced by vertical stress loading in the underlying coal significantly exceeded that in the unloading stage. When the vertical loading stress was below 11 MPa, the coal remained in an elastic stage with minimal damage. Loading between 11~15 MPa corresponded to the yielding stage, witnessing a substantial increase in damage. Loading between 15~18 MPa led to the strengthening stage, the pores and fractures of coal were gradually compacted. Damage variables T can effectively characterize the degree of internal damage of coal. When T=Tc, the internal damage of coal was comparable to that of a coal that has not disturbed by loading and unloading stress.Tc is the damage variable of coal without loading and unloading stress disturbance. When T＞Tc , the coal exhibited a stress-damaged state, with higher values of T corresponding to increasing damage levels. Conversely, when T＜Tc, the coal demonstrated a stress-compacted state, with smaller values of T indicating higher compaction degrees. The degree of stress damage in coal was negatively correlated with the fracture pressure, a high degree of damage made coal more prone to fracture, and it was favor to form the primary hydraulic fractures near the wellbore, which was conducive to hydraulic fracturing. The degree of compaction of coal was positively correlated with fracture pressure. The high degree of compaction weakened the effect of horizontal stress difference on hydraulic fracture expansion, and the hydraulic fracture near the wellbore was more developed, which hindered the formation of primary hydraulic fractures. Based on the research results, the principle of hydraulic fracturing construction scheme optimization for underlying coal seam in goaf was formulated and applied in the field. The hydraulic fracturing ability of the optimized scheme was significantly improved.